Heat Transfer In Automatic Duck Egg Incubator Using A Light Bulb As The Heater - Yanti, Yanti; Rohman, Abd; Patriana, Ari; Fauzi, Willy Muhammad; Mustopa, Asep; Febrian, Rizki Muh (Universitas Muhammadiyah Jakarta, 2023)
The egg incubator is an egg incubator equipped with a heater with a special construction so that the heat in the box is not wasted. This study aims to determine the heat transfer in an automatic egg incubator with incubator dimensions of 0.38 × 0.35 × 0.45 m. The research was conducted by collecting data directly to obtain heat transfer values in automatic egg incubators with a heat source from a light bulb. A digital thermometer was used to measure the temperature of the egg incubator. The incubator temperature was maintained at a maximum temperature of 39°C. Radiation heat transfer that occured in an egg incubator with a surface area of 0.92 m² which was coated with aluminum foil with a material emissivity value of 0.07 and an egg incubator temperature of 39°C (312 K) was 34.6 Watt. The conduction heat transfer that occured on the wall of the egg incubator with the thermal conductivity value of aluminum foil, namely k = 0.034 W/mK, was 34.78 Watt. The results of the study by setting the temperature of the incubator room to a maximum of 39oC obtained a hatching success rate with a hatchability of 75%.